2016
DOI: 10.1111/bjd.14842
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Flightless I expression decreases severity of psoriasis in an imiquimod-induced murine model of psoriasiform dermatitis

Abstract: Flii is a novel target involved in psoriasiform dermatitis and reducing cutaneous Flii could potentially be a new approach for treating patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 28 publications
(46 reference statements)
5
24
0
Order By: Relevance
“…The IMQ mouse model of psoriasiform dermatitis is one of the most utilized animal models in psoriasis research and has phenotypical features of human psoriasis [ 19 ]. Daily application of IMQ cream over a period of 6 days results in increased immune response resulting in erythema, swelling and scales [ 20 ]. While this model is widely used, to the best of our knowledge, this model has only been used to study acute and chronic forms of psoriasis and no previous studies have utilized this model to examine Trm cell levels in acute, chronic and resolved psoriasis-like dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…The IMQ mouse model of psoriasiform dermatitis is one of the most utilized animal models in psoriasis research and has phenotypical features of human psoriasis [ 19 ]. Daily application of IMQ cream over a period of 6 days results in increased immune response resulting in erythema, swelling and scales [ 20 ]. While this model is widely used, to the best of our knowledge, this model has only been used to study acute and chronic forms of psoriasis and no previous studies have utilized this model to examine Trm cell levels in acute, chronic and resolved psoriasis-like dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…LRRFIP-1’s role in TLR signaling and innate inflammatory responses has also been linked to its interactions with a negative regulator of wound healing, Flii, where LRRFIP-1 competes with Flii for the binding to the MyD88 and hence counteracts the effects of Flii on inflammation signaling pathways [ 11 ]. Our studies have investigated the role of Flii as a negative regulator of healing in both acute and chronic wound pathologies and most recently in the inflammatory skin condition psoriasis [ 2 , 16 , 17 , 18 ]. We have also shown that application of Flii-neutralizing antibodies to wounds in vivo neutralizes extracellular Flii, resulting in improved wound re-epithelialization, decreased tissue inflammation, increased cellular proliferation and migration, and significantly decreased early scar formation in both small and large animal models of wound repair [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flii also directly affects the immune response, altering macrophage activation and cytokine production in vitro and increasing Flii expression in diabetic wounds is associated with increased NF-κB production and a prolonged inflammatory phase is observed in the healing of incisional wounds of mice [79][80][81]. The application of a Flii neutralising antibody in an animal model of the inflammatory skin condition, psoriasis, reduces pro-inflammatory cytokine expression and immune cell infiltration [82]. By treating mouse burn wounds with this antibody and reducing the expression of Flii, it was possible to decrease TGF-β1 levels and cause faster wound healing with less scar formation in mice [83] (Figure 4).…”
Section: Interruption Of Immune Signalling Pathwaysmentioning
confidence: 99%